(3eUGHjM GdCfGe aj TQM TQGFY GdESdGes - (3GdHOjQj, GdfLaj, LYaQ Hf CMeO Hf Sja, J (B1369 (3g`s
(3ChdgG (B:s
(3bhdg cJGH GddbWI ; GdedbhW EeG EfSGf hEeG MjhGf Ch ZjQgeG aGdbSe GdChd jSei dbjWG hedbhWG hefHhPG hjfMUQ GdfXQ ajg aj KdGKI ebGUO GdChd aj GddbjW (B...s
(3BNQgG (B:s
.. (3hOaY GdYhV Edi GdGhd Vef GdedJbW dKGfj Ydi cd MGd dGf GdMb KGHJ aj PeJg de jJYjf HGdOaY Edi GdChd hjhVM GdedJbW Ydi GdGhd dJMbb HWdGf GdMce (B...(3bO hbY GdaQGZs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\121s
(3eYLe GdeDdajf (B1\486s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis